2012
DOI: 10.1111/and.12057
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dyslipidaemia and semen quality and serum sex hormone levels: an infertility study of 167 Japanese patients

Abstract: A prospective study was performed in the Reproduction Center of Ichikawa General Hospital (Chiba, Japan) to assess the relationship between dyslipidaemia and sperm quality and serum hormone levels in male patients in Japan. The semen parameters and blood samples were assessed in relation to several variables, including body mass index (BMI) and serum triglyceride (TG) levels. Between 2011 and 2012, 167 male partners of infertile couples aged 22-46 years (mean: 36.5 years) were referred to the reproduction cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…However, it was a surprise that serum lipids levels such as TC, TG, LDL and HDL were almost unrelated to semen parameters except only slightly correlations between serum TG and HDL levels and semen volume, and between serum FFA level and sperm motility. This observation was similar to the results reported by Hagiuda and colleagues [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, it was a surprise that serum lipids levels such as TC, TG, LDL and HDL were almost unrelated to semen parameters except only slightly correlations between serum TG and HDL levels and semen volume, and between serum FFA level and sperm motility. This observation was similar to the results reported by Hagiuda and colleagues [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found, apart from an inverse correlation between (free) T and SAT cell size in univariate analyses, an inverse association of (free) T levels with TG and insulin sensitivity (HOMA-IR). Inverse associations between T levels and TG are consistent with the findings of previous studies [ 29 , 30 ]. Elevated circulating TG levels have been suggested to be an indicator of metabolic derangement, associated with both glucose intolerance and increased amounts of VAT [ 31 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the last years, growing evidence has linked abdominal obesity, insulin resistance and dyslipidemia to male infertility (Kasturi et al ., ; Morrison & Brannigan, ). Several studies suggest that alterations in lipid metabolism may affect semen quality and fertility (Shalaby et al ., ; Saez Lancellotti et al ., ; Bobjer et al ., ; Hagiuda et al ., ). In this context, the model of diet‐induced obesity in rats has been recently used to investigate sperm dysfunction (Ferramosca et al ., ).…”
Section: Introductionmentioning
confidence: 97%